2006
DOI: 10.1039/b608190h
|View full text |Cite
|
Sign up to set email alerts
|

Copper(ii) complexes of terminally protected pentapeptides containing three histidyl residues in alternating positions, Ac-His-Xaa-His-Yaa-His-NH2

Abstract: Copper(II) complexes of the pentapeptides Ac-HisAlaHisValHis-NH2, Ac-HisValHisAlaHis-NH2, Ac-HisProHisAlaHis-NH2, Ac-HisAlaHisProHis-NH2, Ac-HisGlyHisValHis-NH2 and Ac-HisValHisGlyHis-NH2 have been studied by potentiometric, UV-Vis, CD and EPR spectroscopic methods. It has been found that the pentapeptides are efficient ligands for the complexation with copper(II) and exhibit an outstanding versatility in the co-ordination geometry of complexes. The presence of three histidyl residues provides a high possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
74
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 38 publications
17
74
2
Order By: Relevance
“…The determined pK values (see Table 1) representing the deprotonation processes are macroscopic constants and cannot be assigned to individual histidine residues. The pK values are very similar to those measured for other terminally protected short Hisrich peptides [41,42,[48][49][50][51][52], which reflect no specific interaction between the deprotonating groups of the ligands.…”
Section: Protonation Equilibria Of the Ligandssupporting
confidence: 74%
“…The determined pK values (see Table 1) representing the deprotonation processes are macroscopic constants and cannot be assigned to individual histidine residues. The pK values are very similar to those measured for other terminally protected short Hisrich peptides [41,42,[48][49][50][51][52], which reflect no specific interaction between the deprotonating groups of the ligands.…”
Section: Protonation Equilibria Of the Ligandssupporting
confidence: 74%
“…The studies on the copper(II) complexes of the peptide fragments of prion protein and related substances revealed that the internal histidyl residues can also be anchoring sites for copper(II) or nickel(II) binding [5]. Moreover, the formation of polynuclear copper(II) and/or nickel(II) complexes was observed with various multihistidine peptides [8][9][10][11]. Peptide fragments of prion protein and amyloid-β peptides provided the most evident examples for the binding of more than one copper(II) and nickel(II) ions in these complexes [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The value of logKA C H T U N G T R E N N U N G (Cu+3N im ) = 6.47 was obtained for the [CuH 4 L] 6 + species of the 31-mer peptide, while 7.22 and 8.08 were published for the small 3-histidine peptides Ac-HisHisGlyHis-NHMe and Ac-HisAlaHisValHis-NH 2 , respectively; these peptides have similar binding modes. [41,42] According to these data, the stabilities of the macrochelates follow the order HAHVH > HHGH > HuPrPA C H T U N G T R E N N U N G (84-114). The formation of macrochelates with the exclusive metal binding of side-chain imidazole functions have been reported for a series of other peptides that contain two or three histidyl residues and the stability constants were also in the same range.…”
Section: Binding Modes Of the Ligands In Various Speciesmentioning
confidence: 98%
“…The unfavourable consequence is that, because the three binding sites are very similar to each other, the measured EPR spectra resemble those that would be obtained in the case of a system that is formed by a Cu 2 + ion interacting with three ligands that are very similar to each other. In our previous publications [41,42] the parameters A k % 160-170 and 170-180 ( 10 À4 cm…”
Section: Binding Modes Of the Ligands In Various Speciesmentioning
confidence: 99%